Image infrared converters based on ferroelectric- semiconductor thin-layer systems - Sosnin, A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
Some questions concerning pyroelectric sensors application in microphotoelectronics are considered. Data upon main characteristics of different pyroelectric materials (single crystals, ceramics, thin films) are summarized. Also represented are basic parameters of uncooled pyroelectric thermal vision image converters as a promising direction of the infrared engineering.